Diagnosis of accidents in the small and medium mining of Boyacá - González-Sierra, Miguel Alfonso; Lara-González, Luis Ángel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
We report the results of the research project entitled "Awareness and diagnosis of safety in small and medium mining in the departament of Boyacá" which was based on the analysis of accident stadistics provided by the Mining Rescue Station of the National Mining Ageney, Nobsa. The aim of the study is to show the foci and causes of accidents, their frequency and direct relationship witth the coal production in the departament.The results show that the higshest number of accidents in the last decade has ocurred in the provinces of Sugamuxi and Valdarama with 30% and 28% respectively. In turn, the biggest cause of accidental deaths is presented by landslides, causes associated with lightning and ventilation.The analysis concludes that there is a positive correlation between the annual production of coal in the departament and the number of accidents reported to the Mine Rescue Station in Nobsa.